Review of path branch obfuscation - Pu GENG; Yuefei ZHU (网络与信息安全学报)
Code obfuscation is a convenient and effective technique of software protection,which can combat MATE attacks based on reverse engineering.With the development of automatic programming analysis technology,a new code obfuscation technique which named path branch obfuscation was proposed to defeat symbolic execution.With the composition of branch information and how does the branch composition effect in execution technique,the branch obfuscation was classified into three types.Then,a detailed research and development situation of each branch obfuscation class was exhaustively described.At last,the prospects of branch obfuscation were discussed.